Using Motivation, Opportunity, and Ability Model in Social Marketing to Predict "Galamsey" Behavior in Ghana. (March 2020) - Tweneboah-Koduah, Ernest Yaw; Mann, Victoria Ekua; Adams, Matilda
Background: Illegal mining (hereafter referred to as "galamsey") has adverse effect on human life, the environment, and other living organisms that support human existence. However, the traditional strategies employed by governments and other stakeholders to tackle "galamsey" have proved ineffective in changing "galamseyers" behavior. Focus: This research thus aims to apply the motivation, opportunity, and ability (MOA) model in social marketing to predict and explain behavior change toward galamsey activities in Ghana. Specifically, the paper investigates the influence of Motivation (i.e., attitudes toward stopping "galamsey" activities, beliefs and subjective norms) on intentions toward the behavior, as well as opportunity and ability on the intentions–behavior nexus. Key Hypotheses: The study tested the following key hypotheses: There is a positive and significant relationship between beliefs and intention to stop galamsey activities, there is a positive and significant relationship between attitude and intention to stop galamsey activities, there is a positive and significant relationship between social norms and behavioral intention to stop galamsey activities, and there is a positive and significant relationship between intention to stop galamsey and galamsey behavior change. Methods: Self-administered survey was used to collect data from "galamsey" operators ( n = 238) in Kyebi-Ghana, using convenience and snowball sampling techniques. The hypothesized relationships were analyzed using partial least squares structural equation modeling (PLS-SEM). Results: The findings of the study reveal that "galamseyers" behavioral intention toward stopping "galamsey" is mainly determined by the respondents' beliefs about and positive attitudes toward the behavior. The results further establish a positive significant relationship between intention and actual behavior change. Moreover, the findings suggest a strong interactive relationship between intentions and ability, intentions and opportunity and actual behavior. The study however did not find a significant relationship between social norms and intentions to stop "galamsey" activities. Recommendation for Research or Practice: These findings can be used to develop interventions aimed at fostering positive behavior change toward "galamsey." Importance to Social Marketing Field: By applying the MOA model to a social marketing context, the study contributes to knowledge by providing a deeper theoretical understanding from an emerging economy context. Limitation: Although the MOA model was able to predict "galamsey" behavior change, the model has been criticized for including opportunities and failing to mention that inhibitors (barriers) to be reduced to foster sustainable behavior change. Hence, future studies should include other variables in the model to cater for this gap.